The question concerning (internet) time - Leong, Susan; Mitew, Teodor; Celletti, M.; Pearson, Erika (Sage, 2009)
Spatial representations, metaphors and imaginaries (cyberspace, web pages) have been the mainstay of internet research for a long time. Instead of repeating these themes, this paper seeks to answer the question of how we might understand the concept of time in relation to internet research. After a brief excursus on the general history of the concept, this paper proposes three different approaches to the conceptualisation of internet time. The common thread underlying all the approaches is the notion of time as an assemblage of elements such as technical artefacts, social relations and metaphors. By drawing out time in this way, the paper addresses the challenge of thinking of internet time as coexistence, a clash of fluxes, metaphors, lived experiences and assemblages. In other words, this paper proposes a way to articulate internet time as a multiplicity.